Hot Topics in Safety for Pediatric Anesthesia - Amanda N. Lorinc; Camila B. Walters; Hannah K. Lovejoy; Christy J. Crockett; Srijaya K. Reddy (MDPI AG, 2020)
Anesthesiology is one of the leading medical specialties in patient safety. Pediatric anesthesiology is inherently higher risk than adult anesthesia due to differences in the physiology in children. In this review, we aimed to describe the highest yield safety topics for pediatric anesthesia and efforts to ameliorate risk. Conclusions: Pediatric anesthesiology has made great strides in patient perioperative safety with initiatives including the creation of a specialty society, quality and safety committees, large multi-institutional research efforts, and quality improvement initiatives. Common pediatric peri-operative events are now monitored with multi-institution and organization collaborative efforts, such as Wake Up Safe.